Penggunaan media audiovisual dalam pembelajaran menulis teks berita siswa SMP Negeri 1 Siberut Utara - Eva Fitrianti; Novi Fitriani (Universitas Asahan, 2025)
The low proficiency in writing news texts among junior high school students is often attributed to the lack of engaging and contextual learning media. This study aims to describe the news writing skills of eighth-grade students at SMP Negeri 1 Siberut Utara after being taught using audiovisual media. Employing a quantitative approach with a descriptive method, the study involved 50 students selected through random sampling. The research instrument was a news writing test administered after the learning intervention. Data analysis involved reading and reviewing students’ texts, scoring, calculating percentage scores, classifying writing abilities based on a scale of 10, and drawing conclusions. The findings show that the students' average score in writing news texts was 78, indicating a